Measurement of Building Carbon Emissions and Its Decoupling Relationship with the Construction Land Area in China from 2010 to 2020 - Fangjun Xie; Jinhua Cheng; Jianxin Yang; Li Yu; Ji Chai; Deyi Xu (Land)
The building sector is responsible for significant carbon emissions and energy consumption, making it a critical field for global energy-saving and emission reduction efforts to combat climate change. This study calculated the building carbon emissions (BCE) of 30 provinces in the Chinese Mainland from 2010 to 2020 using the IPCC carbon emission factor method based on the statistical data of energy consumption and building materials, and then the decoupling relationship between BCE and the construction land area (CLA) was analyzed. The results are as follows: (1) BCE exhibited an overall increase from 2010 to 2020, yet at a descending rate, with a prominent decrease in indirect BCE (IBCE); (2) BCE and direct BCE (DBCE) were higher in the north but lower in the south, while IBCE was higher along the eastern coast; (3) the provinces in North China and Northeast China possess the largest areas of construction land, but the growth of CLA was the slowest or even declined in the later stage of the study; (4) the decoupling relationship between BCE and CLA is dominated by expansive negative decoupling or strong negative decoupling. The growth of BCE is generally much faster than the expansion of construction land. The findings will have important reference for achieving energy-saving and “dual carbon” strategic development goals in China.